Nasopharyngeal carcinoma treated with intensity-modulated radiotherapy: clinical outcomes and patterns of failure among subsets of 8th AJCC stage IVa - Huang, Cheng-Long; Guo, Rui; Li, Jun-Yan; Xu, Cheng; Mao, Yan-Ping; Tian, Li; Lin, Ai-Hua; Sun, Ying; Ma, Jun; Tang, Ling-long (European radiology, 2020)
Objectives The 8th edition of the American Joint Committee on Cancer (AJCC) staging system for nasopharyngeal carcinoma (NPC) merged T4N0–2 and T1–4N3 to create stage IVa. In the present study, we aimed to assess the difference in clinical outcomes and patterns of failure between 8th AJCC T4N0–2 and T1–4N3 NPC patients treated with intensity-modulated radiotherapy (IMRT). Methods We included 3107 patients with stage IVa NPC disease (1871 with T4N0–2 and 1236 with T1–4N3) according to the 8th AJCC staging system. Overall survival (OS) was the primary endpoint. The clinical outcomes between T4N0–2 and T1–4N3 patients were compared. Results T1–4N3 patients had significantly worse 3-year OS (84.1% vs. 89.2%; p < 0.001) and distant metastasis–free survival (DMFS; 78.3% vs. 85.9%; p < 0.001), but better local relapse–free survival (LRFS; 94.9% vs. 92.2%; p = 0.003), as compared with T4N0–2 patients. Multivariate analysis showed that T1–4N3 was still an independent adverse prognostic factor for both DMFS (hazard ratio [HR] = 1.517, 95% confidence interval [CI] = 1.274–1.806, p < 0.001) and OS (HR = 1.315, 95% CI = 1.100–1.572, p = 0.003), whereas T4N0–2 was an independent adverse prognostic factor for LRFS (HR = 1.581, 95% CI = 1.158–2.158, p = 0.004). Conclusions In terms of the OS, T4N0–2 patients had better prognosis compared with T1–4N3 patients, and the patterns of failure differed between T4N0–2 and T1–4N3 patients. We believe that future modifications of the AJCC/UICC staging system should separate T4N0–2 from T1–4N3. Key Points • In nasopharyngeal carcinoma, T4N0–2 patients tended to develop local relapse, whereas T1–4N3 patients were more likely to develop distant metastasis. • In terms of overall survival, T4N0–2 patients had better prognosis than T1–4N3 patients. • T4N0–2 should be separated from T1–4N3 in the UICC/AJCC staging system.